Exploring tear viscosity with quartz crystal microbalance technology - Muñoz, Gabriel Guillermo (2024)
Tear viscosity is a critical property affecting tear distribution and ocular surface stability. While not widely established as a primary diagnostic marker, deviations from normal viscosity can impact ocular health, potentiallycontributing to conditions like dry eye syndrome. Despite its importance, traditional viscometers require sample volumes that are not feasible to use with tear volume. This research introduces a novel Quartz Crystal Microbalance(QCM)-based method for tear viscosity measurement, offering a viscometer prototype that operates with minimalsample volumes. Human tear samples, solutions used in artificial eye drops, and various commercial eyedrop brands were evaluated. Results show that the QCM method aligns with established viscosity ranges, withhealthy human tears averaging 1.73 ± 0.61 cP, within the typical range of 1 to 10 cP. Variability in eye dropviscosities is attributed to chemical composition differences. QCM measurements of one eye drop brand closelymatch those from a commercial viscometer. The QCM method offers benefits such as reduced sampleconsumption and rapid results, enhancing understanding of tear dynamics for ocular health. Further research withlarger sample sizes is needed to establish normative viscosity values in healthy individuals and those with dry eyesyndrome, crucial for validating the device´s clinical efficacy.